Test Bench for Evaluation of a Soft Robotic Link - Mena, Lisbeth; Monje, Concepción A.; Nagua, Luis; Muñoz, Jorge; Balaguer, Carlos (Frontiers in Robotics and AI, 2020)
In this paper we describe the tests performed at the improved version of one existing soft robotic neck design with two Degrees Of Freedom (DOF), able to achieve flexion, extension and lateral bending movements, similar to those of a human neck. The design is based on a cable-driven mechanism consisting of a spring acting as a cervical spine and three servomotor actuated tendons that let the neck to reach all the desired postures. The prototype was manufactured using a 3D printer and a fractional-order control was implemented for motor position. As the main purpose of this paper, the platform operation has been tested for different load configurations in two ways. On the one hand, real motor position data were gathered through encoder sensors, and on the other hand, the actual tilt and orientation were obtained through an Inertial Measurement Unit (IMU) sensor, allowing the performance comparison from these experimental results, and revealing the need for an external inclination control loop.